2013
DOI: 10.1155/2013/369374
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Endothelial Pencil Graphite Deposition

Abstract: A 14-year-old male patient had an ocular trauma with a pencil. Biomicroscopic examination revealed a broken part of pencil into the cornea. Foreign body removal and corneal wound closure were performed in the same day. After corneal repair, there was a grade 4+ anterior chamber reaction just like in preoperative examination. Dilated examination showed a very small piece broken tip of pencil on the upper nasal quadrant of the lens. A small and linear deposition was also seen on endothelial surface. Endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Penetrating pencil-tip injuries are frequent among children, and the embedded graphite core may increase morbidity or may lead to misdiagnosis. 15,16 As reported in another study, 34 CT was the best imaging modality to detect graphite in the present work. In cases with suspected foreign bodies, conventional plain radiography is usually the initial imaging technique.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Penetrating pencil-tip injuries are frequent among children, and the embedded graphite core may increase morbidity or may lead to misdiagnosis. 15,16 As reported in another study, 34 CT was the best imaging modality to detect graphite in the present work. In cases with suspected foreign bodies, conventional plain radiography is usually the initial imaging technique.…”
Section: Discussionsupporting
confidence: 80%
“…11 Comparatively, tooth, stone and graphite are not so frequent, but they may cause diagnostic worries if left unrecognized. [12][13][14][15][16] When a foreign object accidentally penetrates into the body, it may lodge in an air-filled space, soft tissues or between bones and muscles. 9 Conventional plain radiographs, CT, ultrasonography and MRI are used routinely at trauma settings for detecting and localizing such foreign bodies.…”
Section: Introductionmentioning
confidence: 99%
“… 9 No anterior chamber inflammation occurred during the 1-month follow-up period (with tapering topical steroid and cycloplegic agent as medical therapy). A case reported by Gül et al 8 presented with severely reduced vision (CF at 2 m) following ocular trauma by pencil. On slit-lamp examination, corneal perforation and fragments of pencil lead were observed at the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory reaction induced by inorganic foreign bodies is related to the composition of the object. 1 There are few cases in the literature of intracorneal carbon particles 2 , 3 and intraocular penetrating injuries 4 , 5 , 6 , 7 , 8 due to pencil lead. Although it has been reported that the carbon particles from pencil lead may remain dormant in the eye without inducing inflammation for long periods of time, 2 , 3 they have also been reported to cause severe endophthalmitis5 or endothelial dysfunction and corneal edema.…”
Section: Introductionmentioning
confidence: 99%
“…The main component of pencil is carbon which is thought to remain inert in the eye. There are few cases in the literature of intraocular penetrating injuries with a retained pencil lead intraocular foreign body (IOFB) 3–6. However, there have been reports of pencil lead causing severe inflammatory reaction and endophthalmitis 7.…”
Section: Introductionmentioning
confidence: 99%